Analysis of the Gap Between Perceptions and Competence in Indonesian Language and Its Determining Factors Among Students in the Indonesian Language Program - Syarifudin Yunus; Dewi Indah Susanti (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study aims to analyze the gap between Indonesian Language Program students’ perceptions of their Indonesian language proficiency and to identify the factors that influence this gap. The study employed a quantitative approach using descriptive methods, with research instruments consisting of questionnaires, interviews, and documentary analysis, involving a sample of 42 students from the Indonesian Language Studies Program at Indraprasta PGRI University. Data collection was conducted using simple random sampling. The results revealed a significant gap between the perceptions and actual Indonesian language proficiency of students in the Indonesian Language Studies Program. Although 69% of students assessed their Indonesian language proficiency as good, proficiency assessments showed that only 43% of students demonstrated proficiency in morphology, 40% in syntax, and 40% in semantics. These findings indicate that positive perceptions of language ability do not always align with actual language proficiency. This gap is influenced by both internal and external factors, including learning motivation, interest, self-confidence, the quality of instruction, teaching methods, the social environment, and students’ literacy experiences. Strengthening language proficiency cannot be achieved solely through increasing theoretical knowledge; it requires learning strategies that are more practical, application-oriented, and supported by a culture of sustained literacy. Interest among students in becoming Indonesian language teachers is quite high, reaching 81%, but this needs to be supported by a more targeted and practical improvement in language proficiency. Sustained efforts are needed from the study program to strengthen language learning, enhance literacy practices, and build students’ self-confidence.